Sustainability of Palm Oil Company CSR in Supporting Village Status Change - Dwi Septiyarini; Novira Kusrini; Dewi Kurniati (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
The existence of palm oil companies should have an impact on villages around oil palm companies. However, the status of villages according to the developing village index around oil palm companies are still developing villages. The purpose of this study was to determine the sustainability status of the palm oil company's CSR program in supporting changes in village status. This research was conducted in Kubu Raya Regency with 12 villages and 12 oil palm companies. This study is based on the similarity of indicators between CSR programs and the indicators of the developing village index. The data collected includes primary data and secondary data. The analysis technique uses multidimensional scaling Rapfish. The results of the study show that the sustainability status of the CSR program has the social dimension of unsustainable status with a sustainability value of 24.56, the economic dimension with a value of 57.67 with moderately sustainable status and the environment with a value of 74.27 with moderately sustainable status. The results of the 2019-2021 IDM continue to increase, but the economic resilience index has the lowest value when compared to the social and environmental resilience index.